The generation and characterisation of anti-glycan monoclonal antibodies - Chua, Jia Xin (2017)
Glycomic profiling of tumour tissues consistently shows alterations in N- and O-glycosylation profiles of glycoproteins and glycolipids compared to healthy tissues, with important functional implications for cancer cell biology. Despite the attractiveness of the targets, there are very few mAbs recognising glycans as they induce low affinity IgM responses.